(untitled) (Proceedings of the International Conference on Education, 2023)
The COVID-19 pandemic has led to an unprecedented social isolation responsible for creating a condition on high mental and physical stress and increased anxiety at local and global levels. The ’coronapocalypse’ has imposed new behavioral patterns of social distancing, social isolation and engagement with technology. This virtual interaction has had a significant impact on human nature, having led the world society to a state of digital disorientation, confusion, and often desperation. The current paper reports on a research during the pandemic period, of early 2020 and the following months, aiming to create awareness of the new social conditions brought into the world society by COVID-19, and to identity solutions that would ease the mental strain and provide healthy routines for using technology and for interacting digitally in most aspects of daily life. The research identifies techniques and strategies to cope with digital isolation and disorientation due to physical and social distancing.